Structural and functional characterisation of the group II chaperonin CCT/TRiC - Kelly, J (2020)
Cellular health is dependent on the proper folding of proteins and dysregulation of this pathway can lead to many diseases including neurodegeneration and cancer. This thesis describes efforts undertaken to characterise the mechanism by which one eukaryotic protein chaperonin, CCT/TRiC (TRiC), assists the folding of client substrates. TRiC folds nascent polypeptides using a built-in lid mechanism that can open and close to allow substrate access/restriction in an ATP-dependent manner. TRiC is composed of eight individual subunits, some of which can form synthetic homo-oligomers that retain biological function to a varying degree. The native TRiC complex has proven difficult to isolate recombinantly due to the presence of eight subunits in the complex. Strategies to overcome this difficulty include isolation via nanobody (Nb)-mediated affinity pull-down and by using CRISPR/Cas9 genome editing to insert an affinity tag in the genomic locus of a single TRiC subunit, CCT5, the latter of which can produce large quantities of pure endogenous TRiC from human cells. Structural investigations of native TRiC reveal new details into its substrate-folding mechanism by observing several intermediate states including TRiC-tubulin bound and TRiC-Actin/PhLP2A bound structures. These results suggest a mechanism whereby substrates bind TRiC in an unfolded state and achieve their near-native fold while bound in the closed state. Additionally, the interaction between the co-chaperone PhLP2A and actin shows a novel binding mechanism whereby each TRiC cavity is occupied. These results provide new insights into the TRiC-mediated substrate folding cycle and provide further therapeutic potential for human diseases caused by disruption of proteostasis.